Implementasi Game Interaktif Kahoot dalam Meningkatkan Literasi Siswa Kelas 2 SD - Dinda Astri Pradira; Ambar Wulan Sari; Shofya Sri Harianty (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to determine the use of the Kahoot application in improving the literacy of second grade elementary school students. This research is classroom action research. Data collection was carried out using test and non-test techniques. Test techniques include tests at the end of cycle I and end of cycle II and non-tests include observing student activities and comparing the results of observations and tests. The data analysis technique uses qualitative descriptive. The PTK design applied uses the Kemmis and Mc Taggart (1998) model. The results of this research are that the Kahoot application is very helpful in increasing elementary school students' literacy very significantly. This is because the Kahoot application is an application that is used as a very innovative and interesting learning media technology, especially for elementary school students who are unfamiliar with digital devices.